2013
DOI: 10.1080/10810730.2013.811323
|View full text |Cite
|
Sign up to set email alerts
|

Trust During the Early Stages of the 2009 H1N1 Pandemic

Abstract: Distrust of the government often stands in the way of cooperation with public health recommendations in a crisis. The purpose of this paper is to describe the public’s trust in government recommendations during the early stages of the H1N1 pandemic and identify factors that might account for these trust levels. We surveyed 1543 respondents about their experiences and attitudes related to H1N1 influenza between June 3, 2009 and July 6, 2009, during the first wave of the pandemic using the Knowledge Networks (KN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
128
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 147 publications
(150 citation statements)
references
References 14 publications
7
128
1
4
Order By: Relevance
“…Consistent with Freimuth et al, 13 who investigated trust during the early phase of the pandemic, we found that closely following the news, the quality of communication, and role models were associated with higher trust in government actions and spokespersons. Additionally, we found that the perceived quality of communication has an impact on trust in government actions.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Consistent with Freimuth et al, 13 who investigated trust during the early phase of the pandemic, we found that closely following the news, the quality of communication, and role models were associated with higher trust in government actions and spokespersons. Additionally, we found that the perceived quality of communication has an impact on trust in government actions.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, while elected officials were typically less trusted than public health authorities, President Obama was the next most trusted after the HHS secretary. When we examine only government spokespersons, these findings in the middle of the pandemic are consistent with our results in the early phase of the pandemic, 13 suggesting that there was some stability over time for trust in public health spokespersons at the national, local, and state levels as well as for the president.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations